Antiretroviral Therapy and Sexual Behavior: A Comparative Study between Antiretroviral- Naive and -Experienced Patients at an Urban HIV/AIDS Care and Research Center in Kampala, Uganda - Bateganya, Moses; Colfax, Grant; Shafer, Leigh Anne; Kityo, Cissy; Mugyenyi, Peter; Serwadda, David; Mayanja, Harriet; Bangsberg, David (AIDS Patient Care & STDs, 2005)
We examined whether use of antiretroviral (ARV) therapy is associated with increased sexual risk behavior in a cross-sectional study of patients undergoing ARV therapy (ARV experienced) compared to patients not undergoing ARV therapy (ARV-naïve) attending an urban HIV clinic in Kampala, Uganda. Sexual behavior during the prior 6 months and sexually transmitted disease (STD) treatment was determined by face-to-face structured interviews. Multiple logistic regression was used to identify independent correlates of sexual activity, multiple sexual partners, inconsistent condom use, and STD treatment during the prior 6 months. Three hundred forty-seven (48%) of the 723 respondents reported a history of sexual intercourse in the 6 months prior to the interview (sexually active). Receipt of ARV therapy was not associated with a significantly higher likelihood of being sexually active (adjusted odds ratio [AOR], 2.0 95% confidence interval [CI], 0.3–9.9). Among both ARV-experienced and ARV-naïve persons who were sexually active, 35% (120) reported one or more casual sexual partners in addition to a main partner (no difference by ARV status). Consistent condom use with spouse, regular, casual, and commercial partners was reported by 57%, 65%, 85%, and 85% of the sexually active respondents, respectively. The ARV-experienced respondents were more likely to report consistent condom use with their spouses than were ARV-naïve respondents (OR 2.8295% CI 1.74–4.6). ARV-experienced respondents were more likely than ARV-naïve respondents to have disclosed their HIV status to their spouses (OR 1.57 95% CI 1.07–2.30).The ARV-experienced group was more likely to report STD treatment in the prior 6 months (AOR 2.62 95% CI 1.83.83) than the ARV-naïve group. The findings suggest that in this population, use of ARV therapy was not associated with risky sexual behavior in the prior 6 months. Still, recall and social desirability biases remain important limitations in interpreting these conclusions.